Performance Analysis of Multihop Parallel Free-Space Optical Systems Over Exponentiated Weibull Fading Channels - Ping Wang (IEEE Photonics Journal, 2015)
The performances of multihop parallel free-space optical (FSO) cooperative communication systems with decode-and-forward protocol under exponentiated Weibull (EW) fading channels have been investigated systematically. With the max-min criterion as the best path selection scheme, the probability density function and the cumulative distribution function of the max-min EW random variable are derived. The analytical expressions for the average bit error rate (ABER) and outage probability with identically and independently distributed (i.i.d.) links are then obtained, respectively. Based on it, the ABER for a non-identically and independently distributed (non-i.i.d.) FSO system is also deduced with the help of the Gauss-Laguerre quadrature rule. The ABER performance of the considered system are further analyzed, in detail, under different turbulence conditions, receiver aperture sizes, and structure parameters (R and C). The comparison between i.i.d. and non-i.i.d. FSO systems over EW fading channels shows that the performances of both systems could be improved with large aperture diameters adopted for the structure parameters R and C selected. Monte Carlo simulation is also provided to confirm the correctness of the analytical ABER expressions. This work presents a generalized system model, and it can be used to analyze and design FSO communication systems.